The Meaning of Endeavor and Trust in the Novel Hajar the Secret of the Queen's Heart Zamzam a Perspective on the Hadith - Purwanto, Shinta Ratu Putri Unon; Anwar, Latifah (AMK : Abdi Masyarakat UIKA, 2025)
Humans sometimes have feelings that change according to the situation and conditions they are facing. Every human being has different traits and attitudes, this is what causes a person to have various actions when controlling his emotions. One of the human beings who can be exemplified in responding to things calmly and patiently is Siti Hajar. When faced with a test, he tends to accept and live it as much as possible to the limit of his ability and always involve God in every effort. In Islam, it is called effort and tawakal. The purpose of this research is to provide a deeper understanding of efforts and tawakal, especially through hadith and how it is represented in the novel "Hajar Secrets of the Heart of the Queen of Zamzam". This study uses a library research method with a descriptive qualitative approach. Data sources include the book Saheeh Bukhari No. index 2074, Sunan Tirmidhi index No. 2344, as well as novels and other supporting literature. The result of this research is to be able to apply the meaning of effort and tawakal contained in the hadith narrated by Imam Bukhari and Imam Tirmidhi which is then associated with the story of Siti Hajar in the novel The Secret of the Heart of the Queen Zamzam, thus each individual can apply and emulate Siti Hajar's attitude in applying iktiar and tawakal in daily life.